Novel EEG Biomarker Candidates of Cognitive Dysfunction in Multiple Sclerosis - Giglia, Eileen Rose (Trinity College Dublin. School of Medicine. Discipline of Clinical Medicine, 2025)
Multiple sclerosis (MS) is an autoimmune, inflammatory condition causing myelin damage and axonal degradation. Loss of myelin and axons causes impaired signal propagation throughout the body and impacts sensory and motor functions. Over recent decades, the presence of cognitive symptoms in MS has also been acknowledged. Cognitive impairment is also a frequently reported and distressing symptom of several other neurodegenerative conditions including amyotrophic lateral sclerosis (ALS). Impairments in cognition are now well recognized in these conditions, and an extensive body of research has characterized the extent and domains of this cognitive impairment in each condition. However, measuring and tracking these changes clinically remains a challenge. Clinical measurement of cognitive impairment is generally accomplished through batteries of neuropsychological tests. These tests are extremely useful for diagnosing cognitive dysfunction and can provide information on the severity and the specific domain of the impairment. However, neuropsychological testing is time consuming, requires a trained experimenter, and can be impacted by practice. These factors make neuropsychological testing impractical for frequent or repeated use, such as in a clinical trial. Additionally, the tests do not provide information about underlying neural dysfunction. Electroencephalography (EEG) is a safe, well-tolerated technique to directly measure fast neural activity. It has been proposed as an effective tool to measure biomarkers of cognitive impairment in neurodegenerative disease, and EEG alterations have been observed in MS and ALS. This project sought to use EEG to quantify cognitive changes in MS and to compare these changes with those observed in ALS. 83 people with MS, 74 people with ALS, and 130 healthy controls were included throughout this study. High-density EEG (128-channel) was recorded from each participant during a passive auditory frequency oddball paradigm, the sustained attention to response task (SART), and blocks of resting state with open eyes. Event-related potentials were extracted from the auditory oddball and SART data and compared among people with MS and healthy controls. ERPs were also compared among people with MS, people with ALS, and healthy controls to evaluate whether the similar cognitive In conclusion, EEG can quantify cognitively related neural dysfunction in MS and within MS subtypes. People with MS showed alterations in EEG microstates and in ERPs produced during the SART, but not on an MMN elicited during an auditory oddball. Furthermore, the SART method was shown to be a good tool for longitudinal studies due to its excellent test-retest reliability. These SART ERPs were also shown to be specific to MS, rather than reflective of general neurodegenerative processes. These results pave the way for future longitudinal EEG analysis of cognition in MS with the goal of developing robust biomarkers for the diagnosis, prognosis, and stratification of cognitive impairment in MS.
APPROVED
Keywords: multiple sclerosis; cognitive dysfunction; electroencephalography; biomarker; ERP; microstate; amyotrophic lateral sclerosis